The wars we took to Vietnam : cultural conflict and storytelling - Bates, Milton J. (University of California Press, 1996)
What Americans refer to as the Vietnam War embraces much more than the conflict with North Vietnam. Milton J. Bates considers the other conflicts that Americans brought to that war: the divisions stemming from differences in race, class, sex, generation, and frontier ideology. In exploring the rich vein of writing and film that emerged from the Vietnam War era, he strikingly illuminates how these stories reflect American social crises of the period.